Alkaloids of Chronanthus orientalis (Lois.) Heywood and Frodin (Fabaceae): An Endemic Species of Turkey - Guner, Merve; Yazici, Isin; Karabey, Fatih; Senol, Serdar; Demiray, Hatice (Asian Journal of Chemistry, 2012)
Gas chromatography coupled with mass spectrometry has been used to analyze the alkaloids present in the aerial parts of C. orientalis. Sparteine, lidocaine, oxosparteine, lupanine alkaloids were the major compounds. From the identified four alkaloids, one lidocaine was found for the first time in this endemic plant. Almost all alkaloids belonged to the quinolizidine type.